CREATING A HISTORICAL CHARACTER IN A MUSICAL DRAMA - Ma’murjon To‘rayev (Journals Park Publishing, 2025)
The rich spiritual heritage and exemplary life of our great ancestors, while awakening a deep sense of respect in today’s generation, serves as a source of inspiration for creating artistic works. “Alpomish” epic, a huge monument of folklore, still retains its charm even though it has been more than a thousand years since its creation. This article is about the analysis of the work.
Keywords: Image, actor, theater, skill, audience, play, character, performance.